THE SPIN-ORBIT INTERACTIONS OF ELECTRONS IN QUANTUM DOT - Dineykhan, M.; Zhaugasheva, S.; Imambekov, O.; Sarsembinov, Sh. (Recent Contributions to Physics, 2008)
The alternative method is suggested for taking into account the influence of each layer to explain the mechanism of blocking electrons in a quantum dot . The inclusion of the multilayer structure of nanocrystal leads to additional interactions between electrons in quantum dot and this potential is analytically derived. When the relation of distance of electrons is sufficiently small, the additional potential becomes parabolic. The dependence of frequency of the parabolic potential on the difference of dielectric permeability of layers is determined. We assume that the spin-orbital interactions of electrons in quantum dot are defined in an analogous way as a quarks in the nonrelativistic potential model of hadrons. Starting from this suggestion the spin-orbital interactions of electrons in quantum dot are defined. The dependence of the coupling constant of spin-orbital interactions on the image charge and effective size of quantum dot is studied.